Analysis of the Impact of Industry–School Partnerships and Project-Based Learning on Graduates' Employability at Vocational High Schools in Jakarta - Paramita Andiani; Muhammad Rusdi; Rival Pahrijal (Westscience Press, 2026)
This study examines the impact of industry-school partnerships and project-based learning on the work readiness of vocational high school graduates in Jakarta. A quantitative research design was employed, utilizing a survey distributed to 150 graduates from various vocational schools. The survey measured perceptions of industry-school partnerships, project-based learning, and work readiness using a Likert scale. The data analysis, conducted with SPSS version 25, revealed that both industry-school partnerships and project-based learning have a significant positive relationship with work readiness. Industry-school partnerships were found to enhance technical skills and industry-specific knowledge, while project-based learning fostered critical thinking, problem-solving, and teamwork. The combined effect of these two factors accounted for 29% of the variance in work readiness. The findings suggest that integrating these approaches into vocational education can significantly improve graduates' employability and better prepare them for the workforce. This study provides valuable insights for policymakers and educators aiming to improve vocational education outcomes in Jakarta and beyond.